2009
DOI: 10.1097/aln.0b013e3181bfab7d
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes after Unilateral and Bilateral Total Knee Arthroplasty

Abstract: Background The safety of bilateral total knee arthroplasties (BTKA) during the same hospitalization remains controversial. We sought to study differences in perioperative outcomes between unilateral and BTKA, and further compare BTKAs performed during the same versus different operations during the same hospitalization. Methods Nationwide Inpatient Sample data from 1998 to 2006 were analyzed. Entries for unilateral and BTKA procedures performed on the same day (simultaneous) and separate days (staged) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
122
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(133 citation statements)
references
References 36 publications
(57 reference statements)
9
122
1
1
Order By: Relevance
“…The risk for major morbidity or mortality was comparable among the cohorts after adjustment for significant patient-related factors, which is similar to other studies using large databases finding no significant differences between same-day and staged bilateral TKAs regarding in-hospital [18] and 90-day mortality [28]. However, two meta-analyses [7,22] and the Swedish Knee Arthroplasty Register [26] showed a higher rate of mortality in same-day compared to staged bilateral TKAs.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The risk for major morbidity or mortality was comparable among the cohorts after adjustment for significant patient-related factors, which is similar to other studies using large databases finding no significant differences between same-day and staged bilateral TKAs regarding in-hospital [18] and 90-day mortality [28]. However, two meta-analyses [7,22] and the Swedish Knee Arthroplasty Register [26] showed a higher rate of mortality in same-day compared to staged bilateral TKAs.…”
Section: Discussionsupporting
confidence: 65%
“…In our cohort, the overall rates of procedure-related complications were similar among the bilateral TKA groups, while same-day TKA was associated with lower inhospital infection rate. Prior research has shown that the overall incidence of procedure-related complications was lower after same-day compared to staged bilateral TKAs during a single hospitalization [18]. Likewise, a recent analysis [14] suggested, after risk adjustment, the odds of developing hematoma and infection were lower in patients undergoing same-day bilateral TKAs than in patients undergoing staged bilateral TKAs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations